Penilaian Kinerja Sistem Irigasi Utama Daerah Irigasi Sei Silam - Prasetya, Ririn; Fauzi, Manyuk; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The availability irrigation and drainage systems had to experience a reduction in capability and performance. This is due to lack of maintenance and monitoring for the beginning so it works out of its capacity limit, the low performance of Operations and Maintenances (O & M), deficiency and deteriorating services. Since 2015, the irrigation area Sei Silam has no O & M because of the transfer ofauthority which is from Kampar district government to Riau provincial government. Therefore, it is necessary for evaluating the performance index of facilities and infrastructure in the main irrigation area based on Minister of Public Work Regulation Number 12/PRT/M/2015 which has been interpreted into IrrigationSystem Performance Index (Indeks Kinerja Sistem Irigasi – IKSI). Result of research showed that the performance index is 71.30%or condition of performance is good; where physical infrastructure is in the amount of 31.98%; plantation productivity is equal to 13.02%; supporting facility is 7.7%; personnel organizationis equal to 9.6%; 5% of documentation; also there is 4% in Water User Farmer Association.Keywords: performance index, irrigation, IKSI